Pregnancy Toxaemia in Goat: a Case Report - Bastakoti, R; Pandey, A; Budhathoki, A (Nepalese Veterinary Journal, 2023)
A four years old Khari goat was brought to Madi Veterinary Hospital with the history of parturition 3 days ago with triplet’s kid, in- appetence and weakness. Vitals signs were within normal physiological range. Laboratory diagnosis revealed low glucose level (27 mg/dl) and was diagnosed as pregnancy toxemia on the basis of clinical and laboratory findings. Calcium-borogluconate, corticosteroid, B-complex and jiggery were given as glucose replacement, glucose precursor, metabolic supporter and source of glucose respectively. Goat became responsive with after two days of treatment.